2007
DOI: 10.1074/jbc.m607695200
|View full text |Cite
|
Sign up to set email alerts
|

GABAB Receptor Association with the PDZ Scaffold Mupp1 Alters Receptor Stability and Function

Abstract: ␥-Aminobutyric acid, type B (GABA B ) receptors are heterodimeric G protein-coupled receptors that mediate slow inhibitory synaptic transmission in the central nervous system. To identify novel interacting partners that might regulate GABA B receptor (GABA B R) functionality, we screened the GAB-A B R2 carboxyl terminus against a recently created proteomic array of 96 distinct PDZ (PSD-95/Dlg/ZO-1 homology) domains. The screen identified three specific PDZ domains that exhibit interactions with GABA B R2: Mupp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
80
1

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 79 publications
(86 citation statements)
references
References 55 publications
5
80
1
Order By: Relevance
“…In agreement with these previous studies, here we found that in cultured cortical neurons, 5-HT 2A receptors colocalize with both PSD-95 and MUPP1 in the dendrites and dendritic spines of cortical pyramidal neurons, and when coexpressed in COS-7 cells, MUPP1 facilitates the membrane targeting of 5-HT 2A receptors which can be prevented by mutating the receptor PDZ binding motif. Importantly, MUPP1 is a scaffold for a growing list of synaptic proteins that are involved in GPCR and small GTPase signaling (27,(39)(40)(41). Our data, along with previous studies, are consistent with the roles of both MUPP1 and PSD-95 as protein scaffolds that may integrate signals through GPCRs at the synapse, provide avenues for crosstalk between signaling pathways, and function in the membrane localization of some receptors and signaling proteins.…”
Section: Discussionsupporting
confidence: 90%
“…In agreement with these previous studies, here we found that in cultured cortical neurons, 5-HT 2A receptors colocalize with both PSD-95 and MUPP1 in the dendrites and dendritic spines of cortical pyramidal neurons, and when coexpressed in COS-7 cells, MUPP1 facilitates the membrane targeting of 5-HT 2A receptors which can be prevented by mutating the receptor PDZ binding motif. Importantly, MUPP1 is a scaffold for a growing list of synaptic proteins that are involved in GPCR and small GTPase signaling (27,(39)(40)(41). Our data, along with previous studies, are consistent with the roles of both MUPP1 and PSD-95 as protein scaffolds that may integrate signals through GPCRs at the synapse, provide avenues for crosstalk between signaling pathways, and function in the membrane localization of some receptors and signaling proteins.…”
Section: Discussionsupporting
confidence: 90%
“…Effect of PDZ10 on MT 1 Internalization and DegradationInteraction of GPCRs with PDZ proteins has been shown to stabilize receptors by inhibiting either their constitutive or agonist-promoted internalization (8,34) or by interfering with receptor degradation (4,5). To study the role of MUPP1 in MT 1 internalization and degradation, we used the isolated PDZ10 domain of MUPP1 as a dominant negative to disrupt the MUPP1/MT 1 interaction.…”
Section: Resultsmentioning
confidence: 99%
“…G protein-coupled receptors (GPCRs) 5 constitute the largest family of membrane receptors, and many of the more than 750 members have been shown to interact with PDZ domain-containing proteins, either constitutively or upon agonist activation (2). Binding of PDZ proteins to GPCRs has been reported to primarily regulate subcellular localization, trafficking, and stability of receptors (3).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Second, MAGI-2 overexpression was found to have no effect on ␤ 1 AR-mediated cAMP signaling and to promote agonist-induced ␤ 1 AR internalization (40), but it was found to reduce vasoactive intestinal polypeptide type-1 receptor-mediated cAMP signaling and suppress agonist-induced receptor internalization (41). Finally, although MUPP1 enhances GABA B receptor signaling, it functions to uncouple the melatonin-1 receptor from G␣ i (42,43). Similarly, this study demonstrates that SAP97 regulates CRFR1 trafficking, because overexpression of GFP-SAP97 prevents CRFR1 endocytosis and knockdown of endogenous SAP97 promotes CRFR1 endocytosis.…”
Section: Discussionmentioning
confidence: 98%